Learning a second language through interaction - Ellis, Rod (Studies in bilingualism, 1999)
This book examines different theoretical perspectives on the role that interaction plays in second language acquisition. The principal perspectives are those afforded by the Interaction Hypothesis, Socio-Cultural Theory and the Levels of Processing model. Interaction is, therefore, defined broadly; it is seen as involving both intermental and intramental activity. The theoretical perspectives are explored empirically in a series of studies which investigate the relationship between aspects of interaction and second language acquisition. A number of these studies consider the effects of interac.